Ethanol extract of Gleditsia sinensis thorn suppresses angiogenesis in vitro and in vivo - Yi Jin-Mu; Park Jong-Shik; Oh Se-Mi; Lee Jun; Kim Jinhee; Oh Dal-Seok; Bang Ok-Sun; Kim No Soo (BMC, 2012)
Abstract Background Gleditsia sinensis thorns have been widely used in traditional Korean medicine for the treatment of several diseases, including obesity, thrombosis, and tumor-related diseases. The aim of the study is to determine the antiangiogenic effect of Gleditsia sinensis thorns in vitro and in vivo in a bid to evaluate its potential as an anticancer drug. Methods Ethanol extract of Gleditsia sinensis thorns (EEGS) were prepared and used for in vitro and in vivo assays. In vitro antiangiogenic effect of EEGS was determined in HUVEC primary cells by cell migration and tube formation assays. In vivo antiangiogenic effect of EEGS was determined by measuring vessel formation and vascular endothelial cells migrating into the implanted matrigels in nude mice. The angiogenesis-related proteins of which expression levels were altered by EEGS were identified by proteomic analysis. Results EEGS exerted a dose-dependent antiproliferative effect on HUVEC cells without significant cytotoxicity. Angiogenic properties, such as cell migration and tube formation, were significantly inhibited by EEGS in a dose-dependent manner. New vessel formation was also suppressed by EEGS, as determined by the directed in vivo angiogenesis assays in nude mice. EEGS reduced the expression of proangiogenic proteins, endothelin 1 and matrix metallopeptidase 2, in HUVEC cells. Conclusions Our findings suggest that EEGS can inhibit angiogenesis by down-regulating proangiogenic proteins, and therefore it should be considered as a potential anticancer drug targeting tumor-derived angiogenesis.